Quantifying knowledge spillovers from advances in negative emissions technologies - Giorgio Tripodi; Francesco Lamperti; Roberto Mavilia; Andrea Mina; Francesca Chiaromonte; Fabrizio Lillo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
Negative emissions technologies (NETs) feature prominently in most scenarios that halt climate change and deliver on the Paris Agreement's temperature goal. As of today, however, their maturity and desirability are highly debated. Since the social value of new technologies depends on how novel knowledge fuels practical solutions, we take an innovation network perspective to quantify the multidimensional nature of knowledge spillovers generated by twenty years of research in NETs. In particular, we evaluate the likelihood that scientific advances across eight NET domains stimulate (i) further production of knowledge, (ii) technological innovation, and (iii) policy discussion. Taking as counterfactual scientific advances not related to NETs, we show that NETs-related research generates overall significant, positive knowledge spillovers within science and from science to technology and policy. At the same time, stark differences exist across carbon removal solutions. For example, the ability to turn scientific advances in NETs into technological developments is a nearly exclusively feature of Direct Air Capture (DAC), while Bio-energy with Carbon Capture and Storage (BECCS) lags behind. Conversely, BECCS and Blue Carbon (BC) have gained relative momentum in the policy and public debate, vis-\~A -vis limited spillovers from advances in DAC to policy. Moreover, both scientific advances and collaborations cluster geographically by type of NET, which might affect large-scale diffusion. Finally, our results suggest the existence of coordination gaps between NET-related science, technology, and policy.
Keywords: O30; O38; Q55; Q58; 330; Climate change mitigation; Negative emissions technologies; Carbon dioxide removal; Innovation; Knowledge spillovers; Data mining; Networks